Perception of Spanish consumers towards environmentally friendly labelling in food. (27th October 2019) - Eldesouky, Ali; Mesias, Francisco J.; Escribano, Miguel
Abstract: Food consumption is one of the most important areas to influence environmental sustainability since it is responsible for one third of a household's total environmental impact. However, many consumers are not completely aware of the association between their food consumption and the environmental consequences. Recently, some food companies have developed labelling schemes to help inform their consumers of the impact a specific food product has on the environment during its production. The main objective of this study is to uncover consumers' perceptions and attitudes towards these environmental labels and their impact on consumers' purchase decisions. In this paper, five sustainability labels, covering both ethical and environmental aspects, were chosen as examples. A focus group approach has been taken due to its adequacy to explore beliefs, perceptions and experiences. Four focus group sessions took place with 36 participants in total. The data has been analysed using a specific qualitative program (Atlas.ti). Finally, the findings were presented and discussed in four main sections explained throughout the manuscript: food purchase decision, social and environmental labels, information on labels and reasons for purchase, and lastly, willingness to pay for certified labels. The results of this study show that, although consumers have positive attitudes towards sustainability attributes in food products, constraints still remain that prevent their materialisation in their purchasing behaviour.